Manajemen Kualitas Data dan Informasi Berbantuan Sistem Informasi untuk Meningkatkan Kinerja Operasional Pabrik Pengolahan Kelapa Wawit - Karami, Ahmad Fahmi (Universitas Diponegoro, 2017)
Organizational performance depends on strategic decisions taken by stakeholders in the organization, where strategic decisions of stakeholders depend on the quality of data and information available to the organization. Data and information quality called good when the data and quality has criteria that suits for users of data and information, where data and information user need on the organization will be different according to their aim and objectives, so that the criteria of data quality and information is not universal. The research aims to improve the quality management of data and information by utilizing information systems to produce good quality data and information and help improve the organization's performance on the Palm Oil Processing Factory in Indonesia. This research was conducted to know data and information quality management in producing data and information, and its contribution on the mill performance using interview methods with those who have a role in the implementation of data quality and information management, observation, and document management related to factory performance. This research resulted findings that still in the implementation of data quality and information management there are still procedures that are not undertaken, so the result of data and information not entirely suits with the user wishes. Although the procedure has not been fully implemented, using data and information production has helped data and information users in decision making and succeeded in lowering the mill breakdown by 0.10%.